Stylistic Issues of Modern Dental Scientific Discourse - Astahova, Svitlana; Leshchenko, Tetyana; Zhovnir, Maryna; Shekhavtsova, Svitlana (International Journal of Engineering and Technology, 2018)
The article provides an attempt to reveal and analyze main stylistic issues of scientific dental discourse. As a result of reviewing theoretical and methodological basics of standardizing the language of science and studying discourse fragments, the current state of observing usual word use norms in the course of writing dental scientific discourse texts in different genres: original abstracts, articles, manuals, textbooks, monographs, etc. has been investigated. In addition, the article characterizes cases of incorrect and irrelevant use of language units in professional texts in the dental field and justifies the analysis of dental scientific language correspondence to the basic communicative features of the language. The importance of correct interpretation of scientific facts, modern theories and hypotheses is pointed out. It is also noted that the skillful usage of professional terms is a daily duty of every qualified specialist. The general scientific (induction, deduction, analysis, synthesis, observation, comparison, generalization) and linguistic methods and techniques were used in this scientific work. There was also indicated on irregularity of the professional language of the dental industry. In the article, there were provided arguments and reasonableness for preferred usage of the Ukrainian terms. There was also given a number of national equivalents to the foreign words from the sphere of dentistry.Â Â